EXPERIENCING PLURALISM DALAM INTERKASI PESERTA KURSUS DI KAMPUNG INGGRIS, PARE, KEDIRI - Asep Rahmatullah (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2022)
The discussion about experiencing pluralism in the interaction of course participants Kampung Inggris, Pare, Kediri is interesting to discuss. Several course participants from various different backgrounds become one unit that accepts one another. Differences in religion, ethnicity, culture, etc., do not prevent them from being open to one another. This study uses the phenomenological method and uses Mukti Ali's theory for its analysis. This research concludes that the formation of experiencing pluralism in the sociological dimension of Pare City and the success of experiencing pluralism cannot be separated from religion and local culture.